Effects of Adopting and Adapting Artificial Intelligence-Based Technologies on an ERP IT System - Viorel Costin BANȚA; Raluca Florentina CREȚU; Gabriel Ilie STAICU (CECCAR Business Review)

(untitled)
The emergence and development of emerging technologies, including artificial intelligence, have considerable effects on activities, such as replacing manual and repetitive tasks, using large amounts of data, their analysis using multiple applications and advanced IT systems, developing working solutions in order to natively integrate certain IT systems, which is an aspect that must be considered nowadays. The emergence of ERP (enterprise resource planning) IT systems has succeeded in correlating existing economic activities in a dynamic business environment. This article aims to analyze, design, and implement an automated solution (using existing data in an ERP system, hosted in the cloud) related to an economic sales process used in a company whose line of business is waste recycling. This company collects, stores, and transforms various types of waste into raw material, which is then sold to various companies related to the production area, such as cars, plastics or cables and electrical conductors. Another aspect that has been considered and will be increasingly discussed from now on is the skills required by future employees as regards the use of these smart technologies, also mentioning that universities will have to adapt their teaching programs in order to meet the need for skilled manpower for this working method.